SSZ-51 molecular sieve as well as preparation method and application thereof

By using 2-amino-5-methylpyridine and its quaternary ammonium salt as template agents, the low-toxic SSZ-51 molecular sieve was successfully synthesized, and the industrial application problem of high toxic DMAP limitation in the prior art was solved, efficient catalytic and adsorption performance was achieved, and its application field was expanded.

CN120440911APending Publication Date: 2025-08-08ANHUI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510644638.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-19
Publication Date
2025-08-08

AI Technical Summary

Technical Problem

In the prior art, the synthesis of SSZ-51 molecular sieve relies on the highly toxic and highly polluted organic template agent DMAP, which limits its industrial application and lacks alternative template agents with low toxic and low pollution.

Method used

2-amino-5-methylpyridine and its quaternary ammonium salt or quaternary ammonium base are used as new template agents, combined with aluminum source, phosphorus source, fluorine source and water, and SSZ-51 molecular sieve was synthesized by hydrothermal method, controlling the phosphorus-aluminum ratio between 0.65 and 1.5, controlling the synthesis and calcination conditions, and preparing molecular sieve with specific X-ray diffraction patterns and morphology.

Benefits of technology

The low-toxic and low-pollution SSZ-51 molecular sieve was successfully synthesized, with high specific surface area, adjustable acidic sites and excellent ion exchange capabilities. It is suitable for catalysis, adsorption and medical drug carriers, promoting its industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120440911A_ABST
    Figure CN120440911A_ABST
Patent Text Reader

Abstract

The invention relates to an SSZ-51 phosphorus-aluminum molecular sieve as well as a preparation method and application thereof. In the prior art, the SSZ-51 phosphorus-aluminum molecular sieve only can be synthesized by adopting 4-dimethylaminopyridine as a template agent. According to the present invention, the variety range of the template agent is expanded, and the SSZ-51 molecular sieve is synthesized by using the 2-amino-5-methylpyridine and the quaternary ammonium salt or the quaternary ammonium base thereof; the synthesis raw materials of the molecular sieve comprise an aluminum source, a phosphorus source, a template agent, a fluorine source and water, the molecular sieve has a schematic chemical composition of mAl. NP, and n / m = 0.65-1.5. The molecular sieve disclosed by the invention can be used as a chemical catalyst, a gas adsorbent and a medical drug carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of molecular sieve preparation, and in particular relates to an SSZ-51 molecular sieve and a preparation method and application thereof. Background Art

[0002] In the field of industrial catalysis, molecular sieves are a class of inorganic crystalline materials with a regular pore structure, typically less than 2 nm in diameter. Due to their adjustable chemical composition and acidic sites, excellent thermal and hydrothermal stability, and large specific surface area, molecular sieves exhibit excellent properties in ion exchange, adsorption separation, and shape-selective catalysis. They are widely used in industries such as petrochemicals, natural gas chemicals, fine chemicals, and environmental protection, and are gradually expanding into fields such as optics, electronics, magnetism, medicine, and microelectronics.

[0003] The most commonly used method for synthesizing molecular sieves is the hydrothermal method. The introduction of an organic template is crucial during this hydrothermal synthesis process. Through template effects and structure-directing effects, the template induces the [TO4] tetrahedrons in the synthesis system to condense into specific configurations, thereby constructing molecular sieve materials with specific topologies. Furthermore, templates have multiple synergistic functions: stabilizing the open framework structure through pore filling; balancing the framework's negative charge and regulating the alkaline environment; and inhibiting the excessive incorporation of metal cations through complexation, while enhancing their solubility and promoting the directional synthesis of metal-confined molecular sieves. The rational design of new templates has facilitated the creation of molecular sieves with novel topologies, nanoscale morphologies, and functionalized frameworks. However, some molecular sieves, such as the SSZ-51 molecular sieve, can currently only be synthesized using a single template, severely limiting their industrial application.

[0004] SSZ-51 molecular sieve belongs to SFO type phosphorus aluminum based large pore molecular sieve, its skeleton structure belongs to monoclinic system, space group is C12 / c1, unit cell parameters are: a≈21.7590Å, b≈13.8210Å, c≈14.2237Å, α=90.00°, β=98.849°, γ=90.00°, its skeleton is formed by [PO4] and [AlO4] tetrahedra connected by oxygen bridges, and has a two-dimensional pore structure with twelve-membered rings and eight-membered rings interspersed: the main pores along the

[001] direction are twelve-membered rings with a pore diameter of 6.9Å×7.1Å, providing efficient mass transfer channels; the secondary pores along the

[010] direction are eight-membered rings with a pore diameter of 3.1Å×3.9Å, which enhance the shape selectivity of the molecular sieve. This microporous structure endows SSZ-51 molecular sieve with a high specific surface area (>300m² / g), adjustable acidic sites, and excellent ion exchange and adsorption capabilities. Furthermore, the flexible coordination properties of the PO-Al bonds in its framework provide a structural foundation for the in-situ uniform doping of transition metals (such as Cu and Fe), giving it significant application potential in areas such as n-paraffin isomerization, xylene isomerization, hydroprocessing / cracking, and gas adsorption separation.

[0005] In 2004, the literature (Chemistry of materials, 2004(16): 2844-2851) reported the first successful synthesis of SFO structure SSZ-51 molecular sieve in a phosphorus-aluminum system. The molecular sieve was obtained by static crystallization at 180℃ for two days using 4-dimethylaminopyridine (DMAP) as a template, pseudo-boehmite as an aluminum source, orthophosphoric acid as a phosphorus source, and hydrofluoric acid as a fluorine source. In 2008-2009, the literature (Materials letters, 2008(62): 929-931 and Journal of porous materials, 2009,16(2): 119-127) studied the synthesis of SFO structure molecular sieves using DMAP as a template. It was found that under different synthesis conditions, precursors of SFO structure molecular sieves (such as BPC-1 and EMM-8 molecular sieves) would be induced to form. All precursors would be converted into SFO structure molecular sieves after high temperature calcination. However, the synthesis of SFO molecular sieves in the prior art typically relies on the highly toxic and polluting organic template DMAP, which not only pollutes the environment but also poses potential risks to human health. Currently, no other template agent has been found that can efficiently induce the synthesis of SFO molecular sieves. Therefore, the development of a new template agent with low toxicity and low pollution has important scientific significance and practical value for promoting the early industrial application of SSZ-51 molecular sieves. Summary of the Invention

[0006] The present inventors have conducted diligent research based on the existing technology and invented a new template agent that can guide the synthesis of SSZ-51 molecular sieve, invented a method for using the template agent in the synthesis of SSZ-51 molecular sieve, and further discovered that SSZ-51 molecular sieve has beneficial properties.

[0007] The first aspect of the present invention provides an SSZ-51 molecular sieve, which is synthesized using 2-amino-5-methylpyridine and its quaternary ammonium salt or quaternary ammonium base; the molecular sieve has a schematic chemical composition of mA1·nP, wherein the phosphorus-aluminum ratio n / m is 0.65-1.5;

[0008] The molecular sieve as-synthesized has an X-ray diffraction pattern substantially as shown in Table A-1 below,

[0009] Table A-1

[0010]

[0011] (a): ±0.3°, (b) varies with 2θ;

[0012] The molecular sieve as-synthesized state further comprises at least one diffraction peak in the X-ray diffraction pattern shown in Table A-2 below,

[0013] Table A-2

[0014]

[0015] (a): ±0.3

[0016] As shown in Table A-3 below, the X-ray diffraction pattern is:

[0017] Table A-3

[0018]

[0019] (a): ±0.3°, (b) varies with 2θ;

[0020] The molecular sieve calcined state also includes at least one diffraction peak in the X-ray diffraction pattern shown in Table A-4 below,

[0021] Table A-4

[0022]

[0023] (a): ±0.3°, (b) varies with 2θ.

[0024] Furthermore, the specific surface area of the molecular sieve is 200 to 700 m 3 / g, preferably 350~600m 3 / g; micropore volume is 0.05-0.35 cm3 / g, preferably 0.08-0.25 cm 3 / g, more preferably 0.10-0.22 cm 3 / gram.

[0025] Furthermore, the molecular sieve has a needle-like, long strip-like, or rod-like morphology, preferably a long strip-like or rod-like morphology; a length of 0.2-12 μm, preferably 0.5-8 μm; a width of 0.1-0.5 μm, preferably 0.2-0.4 μm; and a thickness of 0.01-0.1 μm, preferably 0.02-0.05 μm.

[0026] Furthermore, the total acid content of the molecular sieve is not less than 500 μmol / g, preferably 500-1500 μmol / g.

[0027] A second aspect of the present invention provides a method for preparing a molecular sieve, comprising the following steps:

[0028] (1) mixing a phosphorus source, an aluminum source, a fluorine source, an organic template, and water, and then placing the mixture in a crystallization reactor for crystallization treatment, and washing, separating, and drying the crystallized product to obtain a synthesized form of SSZ-51 molecular sieve;

[0029] (2) The synthesized SSZ-51 molecular sieve is calcined to obtain the calcined form of SSZ-51 molecular sieve.

[0030] Furthermore, in step (1), the molar ratio of the aluminum source (calculated as Al2O3), the phosphorus source (calculated as P2O5), the organic template, the fluorine source (calculated as F) and water is 1: (0.25~1.75): (0.05~3): (0.1~1.5): (5~150), preferably 1: (0.5~1.5): (0.1~2.5): (0.1~1.0): (8~80), more preferably 1: (0.75~1.25): (0.5~2): (0.2~0.8): (20~60).

[0031] Furthermore, in step (1), the aluminum source is selected from at least one of aluminum powder, aluminum isopropoxide, aluminum hydroxide, aluminum oxide, pseudo-boehmite, coal gangue, aluminum sulfate, aluminum nitrate, and aluminum chloride; the phosphorus source is selected from at least one of orthophosphoric acid, phosphorous acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, and organic phosphides; and the organic template is selected from the compound of the following structural formula (A), its quaternary ammonium salt, or its quaternary ammonium base form, preferably 2-amino-5-methylpyridine,

[0032]

[0033] Where R1 is C 1-8 Alkyl, preferably C 1-4 Alkyl, more preferably C1-2 Alkyl, most preferably methyl.

[0034] Furthermore, in step (1), the crystallization reactor is selected from at least one of a homogeneous reactor, an oven, and a stirred reactor; the crystallization process is dynamic crystallization or static crystallization with rotation / stirring, the rotation speed is 10-40 rpm, and the stirring speed is 50-200 rpm; the crystallization conditions of the mixture are crystallization at 150-245° C. for 0.5-10 days, preferably crystallization at 180-220° C. for 1-5 days, and more preferably crystallization at 190-210° C. for 1-3 days; The separation method includes at least one of centrifugation or filtration; the drying temperature is 40-250°C, preferably 60-120°C, and the drying time is 8-30 hours, preferably 10-20 hours. The drying can be carried out under normal pressure or under reduced pressure. In step (2), the roasting temperature is 450-700°C, preferably 500-600°C; the roasting time is 3-10 hours, preferably 4-6 hours, and the heating rate during the roasting process is 4-5°C / minute.

[0035] Furthermore, the SSZ-51 molecular sieve may further contain heteroatoms, and the heteroatoms are selected from at least one of Si, Ti, Ge, Mg, Fe, Cu, Zn, and Co.

[0036] Furthermore, the preparation method of the heteroatom-containing SSZ-51 molecular sieve is selected from at least one of direct synthesis, ion exchange, impregnation, and solid grinding; the Si source is selected from at least one of silicic acid, silica sol, sodium silicate, white carbon black, methyl orthosilicate, ethyl orthosilicate, coal gangue, clay, and water glass; the Ti source is selected from at least one of titanium-containing organic metal complexes, titanium salts, and titanium dioxide; the Ge source is selected from at least one of germanium oxide, germanium nitrate, sodium germanate, tetraethyl germanium, and tetraalkoxygermanium; the Mg source is selected from at least one of magnesium-containing organic metal complexes, magnesium salts, magnesium oxide, and magnesium hydroxide; the Fe source is selected from at least one of iron-containing organic metal complexes and iron salts; the Cu source is selected from at least one of copper-containing organic metal complexes, copper salts, copper oxide, and copper hydroxide; the Zn source is selected from at least one of zinc-containing organic metal complexes and zinc salts; and the Co source is selected from at least one of cobalt-containing organic metal complexes and cobalt salts.

[0037] The third aspect of the present invention further provides a molecular sieve composition, comprising the molecular sieve according to any one of the first aspects or the molecular sieve prepared according to any one of the preparation methods described in the second aspect, and other materials.

[0038] Furthermore, the other materials include, for example, active materials and inactive materials. Examples of the active materials include synthetic zeolites and natural zeolites, and examples of the inactive materials (generally referred to as binders) include clay, clay, silica gel, and alumina. These other materials can be used alone or in combination in any proportion. The amounts of the other materials used can be directly referenced to conventional amounts in the art, and are not particularly limited.

[0039] The fourth aspect of the present invention further provides the use of the molecular sieve according to any one of the first aspects, or the molecular sieve prepared according to any one of the preparation methods described in the second aspect, or the molecular sieve composition according to the third aspect as an adsorbent, a catalyst for organic compound conversion, or a medical drug carrier.

[0040] Furthermore, the molecular sieve SSZ-51 or the molecular sieve composition is used as an adsorbent, for example, to separate at least one component from a mixture of multiple components in a gas phase or liquid phase. Thus, at least one component can be partially or substantially completely separated from the mixture of various components by contacting the mixture with the molecular sieve SSZ-51 or the molecular sieve composition, which selectively adsorbs the component.

[0041] Furthermore, the molecular sieve SSZ-51 or the molecular sieve composition can be used as a catalyst, for example, directly or after necessary treatment or conversion (such as ion exchange, etc.) conventionally performed on molecular sieves in the art, as a catalyst (or as a catalytically active component thereof). To this end, according to one aspect of the present invention, for example, reactants (such as hydrocarbons) can be subjected to a predetermined reaction in the presence of the catalyst to obtain a target product.

[0042] Furthermore, the molecular sieve SSZ-51 or the molecular sieve composition is used as a medical drug carrier, for example, it can be applied to drug delivery systems, wound healing, antibacterial and antimicrobial, implant coatings, contrast agents and the like. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The XRD pattern of the molecular sieve (as-synthesized) synthesized in Example 1;

[0044] Figure 2 The XRD spectrum of the molecular sieve (calcined) synthesized in Example 1;

[0045] Figure 3 This is a SEM image of the molecular sieve sample synthesized in Example 1;

[0046] Figure 4 This is the thermogravimetric diagram of the molecular sieve sample synthesized in Example 1;

[0047] Figure 5 This is an SEM image of the molecular sieve sample synthesized in Example 2;

[0048] Figure 6 This is the thermogravimetric diagram of the molecular sieve sample synthesized in Example 8;

[0049] Figure 7 This is the XRD pattern of the molecular sieve (as-synthesized) synthesized in Example 11. DETAILED DESCRIPTION

[0050] The specific embodiments of the present invention are described in detail below. However, it should be noted that the protection scope of the present invention is not limited by these specific embodiments, but is determined by the claims in the appendix.

[0051] All publications, patent applications, patents, and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art. In the event of conflict, the definitions in this specification will prevail.

[0052] When this specification uses the prefix "well known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, the objects introduced by the prefix include those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become generally recognized in the art to be suitable for similar purposes.

[0053] In the context of this specification, except for the contents explicitly stated, any matters or issues not mentioned are directly applicable to those known in the art without any changes. Moreover, any embodiment described herein can be freely combined with one or more other embodiments described herein, and the technical solutions or technical ideas formed thereby are considered part of the original disclosure or original description of the present invention, and should not be regarded as new content not disclosed or anticipated herein, unless a person skilled in the art considers that the combination is obviously unreasonable.

[0054] According to the present invention, the molecular sieve obtained above can be used in any physical form, such as powder, granular or molded product (such as strip, clover, etc.). These physical forms can be obtained in any manner conventionally known in the art and are not particularly limited.

[0055] In the context of this specification, the so-called synthesized state, synthesized form, or synthesized molecular sieve refers to the state of the molecular sieve after synthesis. As an example, the synthesized state may be the state immediately after synthesis (generally referred to as a molecular sieve precursor). In view of this, in the synthesized state, the molecular sieve may contain water and / or may contain organic matter (particularly an organic template).

[0056] In the context of this specification, the term "calcined," "calcined state," or "calcined molecular sieve" refers to the state of the molecular sieve after calcination. Specifically, for example, the calcined state may be the state of the as-synthesized molecular sieve after calcination to further remove organic matter (particularly organic templates) and water that may be present in its pores.

[0057] In the context of this specification, in the XRD data of molecular sieves, w, m, s, and vs represent the diffraction peak intensity, with w being weak, m being medium, s being strong, and vs being very strong, as is well known to those skilled in the art. Generally speaking, w is less than 20; m is 20-40; s is 40-70; and vs is greater than 70.

[0058] In the context of this specification, the structure of the molecular sieve is determined by X-ray diffraction (XRD) patterns, which are measured by X-ray powder diffractometer using a Cu-Kα radiation source and a nickel filter. Prior to sample testing, the crystallization of the molecular sieve sample is observed using a scanning electron microscope (SEM) to confirm that the sample contains only one type of crystal, i.e., that the molecular sieve sample is pure phase. XRD testing is then performed on this basis to ensure that the diffraction peaks in the XRD pattern are free of interference peaks from other crystals.

[0059] In the context of this specification, including in the following examples and comparative examples, the X-ray diffraction pattern (XRD) of the molecular sieve is measured by a Panalytical X PERPRO X-ray powder diffractometer, using a Cu-Kα ray source, a Kα1 wavelength, λ = 1.5405980 angstroms (Å), a nickel filter, a 2θ scanning range of 5 to 40°, an operating voltage of 40 kV, a current of 40 mA, and a scanning rate of 10° / min.

[0060] In the context of this specification, including in the following examples and comparative examples, the morphology of the molecular sieves is measured using a Hitachi S-4800 cold field emission high-resolution scanning electron microscope.

[0061] In the context of this specification, including the following examples and comparative examples, the molecular sieves were analyzed using a Varian 725-ES inductively coupled plasma atomic emission spectrometer (ICP). Sample digestion was performed by dissolving a calcined molecular sieve sample in aqueous hydrofluoric acid, sealing the sample, and allowing it to stand until the solution was clear before testing.

[0062] In the context of this specification, including in the following examples and comparative examples, the determination of the organic template and moisture content in the molecular sieve is carried out by thermal decomposition analysis using a STA449F3-QMS403 thermal analyzer, heating from room temperature to 800°C at a rate of 10°C / min in an air atmosphere.

[0063] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned in this specification are based on weight, unless the weight basis does not conform to the general understanding of those skilled in the art.

[0064] Example 1

[0065] Prepare 7.21 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 2.1628 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 2.30 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.25 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0066] P2O5 / Al2O3=1

[0067] 2-amino-5-methylpyridine / Al2O3=2

[0068] H2O / Al2O3=40

[0069] HF / Al2O3=0.5

[0070] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, stir with a lid for 30 minutes. Remove the lid to release the hydrolyzed alcohol. Add phosphoric acid and stir for 30 minutes, then add hydrofluoric acid and stir for 30 minutes. The polytetrafluoroethylene-lined container containing the reaction mixture is sealed in a stainless steel autoclave. The autoclave is then placed in a homogeneous reactor and crystallized at 200°C and 20 rpm for 3 days. After crystallization is complete and the autoclave temperature drops to room temperature, the crystallized product is removed and filtered or centrifuged. The resulting solid phase is washed with deionized water until the pH is near neutral (pH = 7-8). The as-synthesized molecular sieve is dried in a 100°C oven for 12 hours, followed by calcination at 550°C in air for 6 hours to obtain the calcined molecular sieve.

[0071] The XRD spectrum of the synthesized product is as follows Figure 1 As shown, the XRD spectrum of the calcined product is as follows Figure 2 As shown, the product is pure phase SSZ-51 aluminum phosphorus molecular sieve. The SEM electron microscope image of the product is as follows Figure 3 As shown, the crystals are in the form of long strips with a length of 1~8μm, a width of 0.2~0.4μm and a thickness of 0.02~0.05μm. The P2O5 / Al2O3 molar ratio of the calcined SSZ-51 molecular sieve was measured by inductively coupled plasma atomic emission spectrometry to be 0.92. The thermogravimetric curve of the SSZ-51 molecular sieve measured by thermal analyzer is shown in Figure 1. Figure 4 As shown, the synthesized SSZ-51 molecular sieve contains 1% water and 15.49% organic template.

[0072] Example 2

[0073] Prepare 5.40 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 2.1628 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 1.73 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.25 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0074] P2O5 / Al2O3=0.75

[0075] 2-amino-5-methylpyridine / Al2O3=2

[0076] H2O / Al2O3=30

[0077] HF / Al2O3=0.5

[0078] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, cover and stir for 20 minutes. Remove the cover to release the hydrolyzed alcohol. Add phosphoric acid and stir for 20 minutes, then add hydrofluoric acid and stir for 20 minutes. Cover the polytetrafluoroethylene-lined container containing the reaction mixture, seal it in a stainless steel autoclave, and place the autoclave in a homogeneous reactor for crystallization at 190°C and 20 rpm for 4 days. After crystallization is complete and the autoclave temperature drops to room temperature, remove the crystallized product, filter or centrifuge, and wash the resulting solid phase with deionized water until the pH is near neutral (pH = 7-8). Dry in a 90°C oven for 12 hours to obtain the synthesized molecular sieve, which is then calcined in air at 550°C for 6 hours to obtain the calcined molecular sieve.

[0079] The obtained molecular sieve was analyzed by X-ray diffractometer and the morphology of the molecular sieve was observed by SEM electron microscope. The test results showed that the sample was pure phase SSZ-51 phosphorus aluminum molecular sieve with morphology as shown in FIG. Figure 5As shown, the material is a flat, elongated aggregate. The P2O5 / Al2O3 molar ratio of the calcined SSZ-51 molecular sieve, as measured by inductively coupled plasma atomic emission spectrometry, is 0.69. Thermal analysis reveals that the as-synthesized SSZ-51 molecular sieve contains 0.42% water and 18.44% organic template.

[0080] Example 3

[0081] Prepare 7.21 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 1.6221 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 1.96 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.25 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0082] P2O5 / Al2O3=0.85

[0083] 2-amino-5-methylpyridine / Al2O3=1.5

[0084] H2O / Al2O3=40

[0085] HF / Al2O3=0.5

[0086] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, stir with a lid for 30 minutes. Remove the lid to release the hydrolyzed alcohol. Add phosphoric acid and stir for 30 minutes, then add hydrofluoric acid and stir for 40 minutes. The polytetrafluoroethylene-lined container containing the reaction mixture is sealed in a stainless steel autoclave. The autoclave is then placed in a homogeneous reactor and crystallized at 200°C and 30 rpm for 2 days. After crystallization is complete and the autoclave temperature drops to room temperature, the crystallized product is removed and filtered or centrifuged. The resulting solid phase is washed with deionized water until the pH is near neutral (pH = 7-8). The as-synthesized molecular sieve is dried in a 90°C oven for 10 hours, followed by calcination in air at 550°C for 6 hours to obtain the calcined molecular sieve.

[0087] The resulting molecular sieve was analyzed using an X-ray diffractometer and its morphology was observed using a scanning electron microscope (SEM). The test results indicated that the sample was a pure-phase SSZ-51 aluminum-phosphorus molecular sieve with the morphology of elongated aggregates. The P2O5 / Al2O3 molar ratio of the calcined SSZ-51 molecular sieve was 0.80, as measured by inductively coupled plasma atomic emission spectrometry. A thermal analyzer determined that the as-synthesized SSZ-51 molecular sieve contained 1.0% moisture and 16.32% organic template.

[0088] Example 4

[0089] Prepare 9.01 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 1.0814 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 2.19 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.38 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0090] P2O5 / Al2O3=0.95

[0091] 2-amino-5-methylpyridine / Al2O3=1

[0092] H2O / Al2O3=50

[0093] HF / Al2O3=0.75

[0094] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, stir with a lid for 30 minutes. Remove the lid to release the hydrolyzed alcohol. Add phosphoric acid and stir for 30 minutes, then add hydrofluoric acid and stir for 30 minutes. Seal the polytetrafluoroethylene-lined container containing the reaction mixture in a stainless steel autoclave. Place the autoclave in a homogeneous reactor and crystallize at 190°C and 20 rpm for 3 days. Once crystallization is complete and the autoclave temperature drops to room temperature, remove the crystallized product, filter or centrifuge, and wash the resulting solid phase with deionized water until the pH is near neutral (pH = 7-8). Dry in a 100°C oven for 10 hours to obtain the synthesized molecular sieve, which is then calcined in air at 550°C for 6 hours to obtain the calcined molecular sieve.

[0095] The resulting molecular sieve was analyzed using an X-ray diffractometer and its morphology was observed using a scanning electron microscope (SEM). The test results indicated that the sample was a pure SSZ-51 aluminum-phosphorus molecular sieve with an elongated strip-like morphology. The P2O5 / Al2O3 molar ratio in the calcined state of the SSZ-51 molecular sieve was 0.80, as measured by inductively coupled plasma atomic emission spectrometry. A thermal analyzer determined that the as-synthesized SSZ-51 molecular sieve contained 1.24% water and 15.87% organic template.

[0096] Example 5

[0097] Prepare 10.81 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 0.9192 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 2.54 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.25 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0098] P2O5 / Al2O3=1.1

[0099] 2-amino-5-methylpyridine / Al2O3=0.85

[0100] H2O / Al2O3=60

[0101] HF / Al2O3=0.5

[0102] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, cover and stir for 20 minutes. Remove the cover to release the hydrolyzed alcohol. Add phosphoric acid and stir for 20 minutes, then add hydrofluoric acid and stir for 40 minutes. Cover the polytetrafluoroethylene-lined container containing the reaction mixture and seal it in a stainless steel autoclave. Place the autoclave in a homogeneous reactor and crystallize at 200°C and 20 rpm for 1 day. After crystallization is complete and the autoclave temperature drops to room temperature, remove the crystallized product, filter or centrifuge, and wash the resulting solid phase with deionized water until the pH is near neutral (pH = 7-8). Dry in a 120°C oven for 12 hours to obtain the synthesized molecular sieve, which is then calcined in air at 550°C for 6 hours to obtain the calcined molecular sieve.

[0103] The resulting molecular sieve was analyzed using an X-ray diffractometer and its morphology was observed using a scanning electron microscope (SEM). The test results indicated that the sample was a pure SSZ-51 aluminum-phosphorus molecular sieve with a rod-like morphology. The P2O5 / Al2O3 molar ratio in the calcined state of the SSZ-51 molecular sieve was 1.02, as measured by inductively coupled plasma atomic emission spectrometry. A thermal analyzer determined that the as-synthesized SSZ-51 molecular sieve contained 1.0% moisture and 15.46% organic template.

[0104] Example 6

[0105] Prepare 14.41 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 2.1628 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 2.77 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.25 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0106] P2O5 / Al2O3=1.2

[0107] 2-amino-5-methylpyridine / Al2O3=2

[0108] H2O / Al2O3=80

[0109] HF / Al2O3=0.5

[0110] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, stir with a lid for 30 minutes. Remove the lid to release the hydrolyzed alcohol. Add phosphoric acid and stir for 30 minutes, then add hydrofluoric acid and stir for 30 minutes. Seal the polytetrafluoroethylene-lined container containing the reaction mixture in a stainless steel autoclave. Place the autoclave in a homogeneous reactor and crystallize at 195°C and 30 rpm for 2 days. Once crystallization is complete and the autoclave temperature drops to room temperature, remove the crystallized product, filter or centrifuge, and wash the resulting solid phase with deionized water until the pH is near neutral (pH = 7-8). Dry in a 100°C oven for 11 hours to obtain the synthesized molecular sieve, which is then calcined in air at 600°C for 5 hours to obtain the calcined molecular sieve.

[0111] The resulting molecular sieve was analyzed using an X-ray diffractometer and its morphology was observed using a scanning electron microscope (SEM). The test results indicated that the sample was a pure-phase SSZ-51 aluminum-phosphorus molecular sieve with a rod-like morphology. The P2O5 / Al2O3 molar ratio in the calcined state of the SSZ-51 molecular sieve was 1.09, as measured by inductively coupled plasma atomic emission spectrometry. A thermal analyzer determined that the as-synthesized SSZ-51 molecular sieve contained 1.5% water and 16.24% organic template.

[0112] Example 7

[0113] Prepare 7.21 g of deionized water, 4.1279 g of aluminum isopropoxide (containing 99 wt% of aluminum isopropoxide), 1.0814 g of 2-amino-5-methylpyridine (containing 98 wt% of 2-amino-5-methylpyridine), 4.61 g of phosphoric acid (containing 85 wt% of phosphoric acid), and 0.13 g of hydrofluoric acid (containing 40 wt% of hydrofluoric acid). The material ratio (molar ratio) of the reactants is:

[0114] P2O5 / Al2O3=2

[0115] 2-amino-5-methylpyridine / Al2O3=1

[0116] H2O / Al2O3=40

[0117] HF / Al2O3=0.25

[0118] After thoroughly mixing deionized water, 2-amino-5-methylpyridine, and aluminum isopropoxide, stir with a lid for 30 minutes. Remove the lid to release the hydrolyzed alcohol. Add phosphoric acid and stir for 30 minutes, then add hydrofluoric acid and stir for 30 minutes. The polytetrafluoroethylene-lined container containing the reaction mixture is sealed in a stainless steel autoclave. The autoclave is then placed in a homogeneous reactor and crystallized at 200°C and 30 rpm for 3 days. After crystallization is complete and the autoclave temperature drops to room temperature, the crystallized product is removed and filtered or centrifuged. The resulting solid phase is washed with deionized water until the pH is near neutral (pH = 7-8). The as-synthesized molecular sieve is dried in a 100°C oven for 12 hours, followed by calcination in air at 600°C for 6 hours to obtain the calcined molecular sieve.

[0119] The obtained molecular sieve was subjected to phase analysis using an X-ray diffractometer, and the test results showed that the sample was amorphous.

[0120] Example 8

[0121] The reaction materials and reaction conditions were the same as those in Example 1, except that 0.150 g of silica sol (containing 40% by weight of silicon dioxide) was added. The material ratio (molar ratio) of the reactants was:

[0122] P2O5 / Al2O3=1

[0123] 2-amino-5-methylpyridine / Al2O3=2

[0124] H2O / Al2O3=40

[0125] HF / Al2O3=0.5

[0126] SiO2 / Al2O3=0.1

[0127] The obtained molecular sieve was analyzed by X-ray diffractometer and the morphology of the molecular sieve was observed by SEM electron microscope. The test results showed that the sample was pure phase SSZ-51 phosphorus aluminum molecular sieve with rod-like morphology. The P2O5 / Al2O3 molar ratio of the calcined SSZ-51 molecular sieve was 0.89 by inductively coupled plasma atomic emission spectrometry. The water content of the synthesized SSZ-51 molecular sieve was 1.0% and the organic template was 16.5% by thermal analyzer. Figure 6 shown.

[0128] Example 9

[0129] The reaction materials and reaction conditions were the same as those in Example 1, except that 0.4032 g of zinc acetate dihydrate (containing 83.60 wt % zinc acetate) was also prepared. The material ratio (molar ratio) of the reactants was:

[0130] P2O5 / Al2O3=1

[0131] 2-amino-5-methylpyridine / Al2O3=2

[0132] H2O / Al2O3=40

[0133] HF / Al2O3=0.5

[0134] Zn / Al2O3=0.2

[0135] The obtained product was subjected to phase analysis using an X-ray diffractometer, and the test results showed that the sample was a pure phase SSZ-51 aluminum-phosphorus molecular sieve.

[0136] Example 10

[0137] The reaction materials and reaction conditions were the same as those in Example 1, except that 0.7033 g of copper sulfate pentahydrate (containing 64% by weight of copper sulfate) was also prepared. The material ratio (molar ratio) of the reactants was:

[0138] P2O5 / Al2O3=1

[0139] 2-amino-5-methylpyridine / Al2O3=2

[0140] H2O / Al2O3=40

[0141] HF / Al2O3=0.5

[0142] Cu / Al2O3=0.2

[0143] The obtained product was subjected to phase analysis using an X-ray diffractometer, and the test results showed that the sample was a pure phase SSZ-51 aluminum-phosphorus molecular sieve.

[0144] Example 11

[0145] The reaction materials and reaction conditions were the same as in Example 1, except that hydrofluoric acid was not added. The material ratio (molar ratio) of the reactants was:

[0146] P2O5 / Al2O3=1

[0147] 2-amino-5-methylpyridine / Al2O3=2

[0148] H2O / Al2O3=40

[0149] The product was tested by X-ray diffractometer, and the results were as follows: Figure 7 As shown, the obtained product is aluminophosphate.

Claims

1. An SSZ-51 aluminum-phosphorus molecular sieve synthesized from 2-amino-5-methylpyridine and its quaternary ammonium salt or quaternary ammonium base; the molecular sieve has a schematic chemical composition of mA1·nP, wherein the phosphorus-aluminum ratio n / m is 0.65-1.5; The molecular sieve as-synthesized has an X-ray diffraction pattern substantially as shown in Table A-1 below, Table A-1 (a): ±0.3°, (b) varies with 2θ; The molecular sieve as-synthesized state further comprises at least one diffraction peak in the X-ray diffraction pattern shown in Table A-2 below, Table A-2 (a): ±0.3°, (b) varies with 2θ; The molecular sieve calcined state has an X-ray diffraction pattern substantially as shown in Table A-3 below, Table A-3 (a): ±0.3°, (b) varies with 2θ; The molecular sieve calcined state also includes at least one diffraction peak in the X-ray diffraction pattern shown in Table A-4 below, Table A-4 (a): ±0.3°, (b) varies with 2θ.

2. The aluminum-phosphorus molecular sieve according to claim 1, characterized in that The molecular sieve has a needle-like, strip-like, or rod-like morphology, preferably a strip-like or rod-like morphology.

3. The aluminum-phosphorus molecular sieve according to claim 1, characterized in that The synthesis method comprises the following steps: (1) mixing a phosphorus source, an aluminum source, a fluorine source, an organic template, and water, and then placing the mixture in a crystallization reactor for crystallization treatment, and washing, separating, and drying the product to obtain a synthesized form of SSZ-51 molecular sieve; (2) The synthesized SSZ-51 molecular sieve is calcined to obtain the calcined form of SSZ-51 molecular sieve.

4. The preparation method according to claim 3, characterized in that In step (1), the molar ratio of the aluminum source (calculated as Al2O3), the phosphorus source (calculated as P2O5), the organic template, the fluorine source (calculated as F) and water is 1: (0.25~1.75): (0.05~3): (0.1~1.5): (5~150), preferably 1: (0.5~1.5): (0.1~2.5): (0.1~1.0): (8~80), more preferably 1: (0.75~1.25): (0.5~2): (0.2~0.8): (20~80).

5. The preparation method according to claim 3, characterized in that: In step (1), the aluminum source is selected from at least one of aluminum powder, aluminum isopropoxide, aluminum hydroxide, aluminum oxide, pseudo-boehmite, coal gangue, aluminum sulfate, aluminum nitrate, and aluminum chloride; the phosphorus source is selected from at least one of orthophosphoric acid, phosphorous acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, and organic phosphides; the fluorine source is selected from at least one of hydrofluoric acid and ammonium fluoride; and the organic template is selected from the compound of the following structural formula (A), its quaternary ammonium salt, or its quaternary ammonium base form, preferably 2-amino-5-methylpyridine, (A) Where R1 is C 1-8 Alkyl, preferably C 1-4 Alkyl, more preferably C 1-2 Alkyl, most preferably methyl.

6. The preparation method according to claim 3, characterized in that: In step (1), the crystallization reactor is selected from at least one of a homogeneous reactor, an oven, and a stirred reactor; the crystallization process is a dynamic crystallization or a static crystallization with rotation / stirring, the rotation speed is 10 to 40 rpm, and the stirring speed is 50 to 200 rpm; the crystallization conditions of the mixture are crystallization at 150 to 245° C. for 0.5 to 10 days, preferably crystallization at 180 to 220° C. for 1 to 5 days, more preferably crystallization at 190 to 210° C. for 1 to 3 days; the separation The separation method includes at least one of centrifugation or filtration; the drying temperature is 40-250° C., preferably 60-120° C., the drying time is 8-30 hours, preferably 10-20 hours, and the drying can be carried out under normal pressure or under reduced pressure; in step (2), the roasting temperature is 450-700° C., preferably 500-600° C.; the roasting time is 3-10 hours, preferably 4-6 hours, and the heating rate during the roasting process is 4-5° C. / minute.

7. The molecular sieve SSZ-51 according to claim 1, characterized in that The molecular sieve may further contain heteroatoms, and the heteroatoms are selected from at least one of Si, Ti, Ge, Mg, Fe, Cu, Zn, and Co.

8. The heteroatom-containing SSZ-51 molecular sieve according to claim 7, characterized in that: The preparation method of the heteroatom-containing SSZ-51 molecular sieve is selected from at least one of direct synthesis, ion exchange, impregnation, and solid grinding; the Si source is selected from at least one of silicic acid, silica sol, sodium silicate, white carbon black, methyl orthosilicate, ethyl orthosilicate, coal gangue, clay, and water glass; the Ti source is selected from at least one of titanium-containing organic metal complexes, titanium salts, and titanium dioxide; the Ge source is selected from at least one of germanium oxide, germanium nitrate, sodium germanate, tetraethyl germanium, and tetraalkoxygermanium; the Mg source is selected from at least one of magnesium-containing organic metal complexes, magnesium salts, magnesium oxide, and magnesium hydroxide; the Fe source is selected from at least one of iron-containing organic metal complexes and iron salts; the Cu source is selected from at least one of copper-containing organic metal complexes, copper salts, copper oxide, and copper hydroxide; the Zn source is selected from at least one of zinc-containing organic metal complexes and zinc salts; and the Co source is selected from at least one of cobalt-containing organic metal complexes and cobalt salts.

9. A molecular sieve composition comprising the molecular sieve according to any one of claims 1 to 2 or the molecular sieve prepared according to the preparation method according to any one of claims 3 to 8, and other materials.

10. Use of the molecular sieve according to any one of claims 1 to 2, or the molecular sieve prepared according to the preparation method according to any one of claims 3 to 8, or the molecular sieve composition according to claim 9 as an adsorbent, catalyst or medical drug carrier.